The effects of surface fossil magnetic fields on massive star evolution – II. Implementation of magnetic braking in mesa and implications for the evolution of surface rotation in OB stars. Issue 1 (25th January 2020) - Keszthelyi, Z; Meynet, G; Shultz, M E; David-Uraz, A; ud-Doula, A; Townsend, R H D; Wade, G A; Georgy, C; Petit, V; Owocki, S P
ABSTRACT: The time evolution of angular momentum and surface rotation of massive stars are strongly influenced by fossil magnetic fields via magnetic braking. We present a new module containing a simple, comprehensive implementation of such a field at the surface of a massive star within the Modules for Experiments in Stellar Astrophysics (mesa ) software instrument. We test two limiting scenarios for magnetic braking: distributing the angular momentum loss throughout the star in the first case, and restricting the angular momentum loss to a surface reservoir in the second case. We perform a systematic investigation of the rotational evolution using a grid of OB star models with surface magnetic fields ( M ⋆  = 5–60 M⊙, Ω/Ωcrit  = 0.2–1.0, B p  = 1–20 kG). We then employ a representative grid of B-type star models ( M ⋆  = 5, 10, 15 M⊙, Ω/Ωcrit  = 0.2, 0.5, 0.8, B p  = 1, 3, 10, 30 kG) to compare to the results of a recent self-consistent analysis of the sample of known magnetic B-type stars. We infer that magnetic massive stars arrive at the zero-age main sequence (ZAMS) with a range of rotation rates, rather than with one common value. In particular, some stars are required to have close-to-critical rotation at the ZAMS. However, magnetic braking yields surface rotation rates converging to a common low value, making it difficult to infer the initial rotation rates of evolved, slowly rotating stars.